IOT BASED PLANT MONITORING SYSTEM USING TELEGRAM BOT - S, Mounika; A, Anitha; B, Jayalakshmi; Y, Prabhavathamma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
More and more it has become necessary to use technologies in the agriculture field. Agriculture is the backbone of our country; most of the people depend on agriculture. The main issue in agriculture is water scarcity. The water resource is not used in an effective manner, so the water is wasted. In order to overcome this irrigation process can be automated. The use of Internet of things in this field will be helpful to reduce the wastage of water. The use of sensors for IoT and actuators that make everything in the field more efficient and modern. We can do work easily and efficiently. The work can also be done within a very short period. By developing this intelligent system aimed at monitoring and controlling soil moisture in plants and plantations, it not only speeds up the work but also reduces the wastage of water by supplying required amount of water to the plant. It sends Telegram message which contains the details of the water content in the plant and can be viewed whenever we want.